Stakeholders’ participation intention towards a sustainable destination management system - Anh, Lle Thi Phuong; Kunasekaran, Puvaneswaran; Ragavan, Neethiahnathan Ari; Subramaniam, Thanam; Thomas, Tony K. (Penerbit Universiti Malaysia Terengganu, 2022)
This study aims to predict the intention to participate in the Destination Management System (DMS) among tourism stakeholders in Vietnam. By using and modifying the Unified Theory of Acceptance and Use of Technology (UTAUT) for organisational level, this paper will identify and empirically examine factors that influence various stakeholders that are potential users of DMS to adopt and accept a comprehensive national DMS in Vietnam. A convenience sampling method was used to collect data from tourism-related stakeholders in Vietnam. 301 questionnaires were used in the study. This data was analysed using structural equation modeling with Smart PLS. The results showed that the important predictors of the tourism stakeholder’s participation in the DMS included social influence, government regulations and technology awareness. Interestingly, technology awareness was found to mediate the relationship between performance expectancy, social influence and the intention to participate in the DMS. The study provides recommendations to DMS developers, potential DMS managers and national tourism authorities in developing a sustainable destination management system, and highlights limitations of the study as well as suggestions for future research.